Regional variations in occupancy frequency distribution patterns between odonate assemblages in Fennoscandia - Esa Korkeamäki; Merja Elo; Göran Sahlén; Jukka Salmela; Jukka Suhonen (WILEY, 2022)
Odonate (damselfly and dragonfly) species richness and species occupancy frequency distributions (SOFDs) were analyzed in relation to geographical location in standing waters (lakes and ponds) in Fennoscandia, from southern Sweden to central Finland. In total, 46 dragonfly and damselfly species were recorded from 292 waterbodies. Species richness decreased to the north and increased with waterbody area in central Finland, but not in southern Finland or in Sweden. Species occupancy ranged from 1 up to 209 lakes and ponds. Over 50% of the species occurred in <10% of the waterbodies, although this proportion decreased to the north. In the southern lakes and ponds, none of the species occurred in all lakes, whereas in the north, many species were present in all of the studied waterbodies. The dispersal ability of the species did not explain the observed species occupancy frequencies, but generalist species with a large geographical range occurred in a higher percentage of the waterbodies. At Fennoscandia scale, we found that the unimodal satellite pattern was predominant. However, at smaller scale, we found geographical variations in odonate species SOFD patterns. The most southern communities followed the unimodal satellite-dominant pattern, whereas in other regions, communities fitted best with the bimodal core-satellite patterns. It seems that the richer species pool in the southern locations, and the larger distribution range of the northern species, skewed the unimodal pattern into a bimodal satellite-dominant pattern.